An iridium(iii/iv/v) redox series featuring a terminal imido complex with triplet ground state. Issue 18 (25th April 2018) - Kinauer, Markus; Diefenbach, Martin; Bamberger, Heiko; Demeshko, Serhiy; Reijerse, Edward J.; Volkmann, Christian; Würtele, Christian; van Slageren, Joris; de Bruin, Bas; Holthausen, Max C.; Schneider, Sven
Abstract : An iridium(iii –v ) imido series has been isolated that features an iridium complex with an unprecedented triplet ground state. Abstract : The iridium(iii /iv /v ) imido redox series [Ir(N t Bu)N(CHCHP t Bu2 )2 ] 0/+/2+ was synthesized and examined spectroscopically, magnetically, crystallographically and computationally. The monocationic iridium(iv ) imide exhibits an electronic doublet ground state with considerable 'imidyl' character as a result of covalent Ir–N t Bu bonding. Reduction gives the neutral imide [Ir(N t Bu)N(CHCHP t Bu2 )2 ] as the first example of an iridium complex with a triplet ground state. Its reactivity with respect to nitrene transfer to selected electrophiles (CO2 ) and nucleophiles (PMe3 ), respectively, is reported.